Methods, Theories, and Empirical Applications in the Social Sciences
351 p. 21 illus.
Keywords: The volume addresses major features in empirical social research from methodological and theoretical perspectives. Prominent researchers discuss central problems in empirical social research in a theory-driven way from political science, sociological or social-psychological points of view. These contributions focus on a renewed discussion of foundations together with innovative and open research questions or interdisciplinary research perspectives.